Canopy closure altered biomass allocation in young spruce stand - B. Konôpka; J. Pajtík; R. Marušák (Journal of Forest Science, 2015)
Growth intensity of particular tree components is controlled by a variety of factors and as a consequence, biomass allocation also changes over time. Since allocation of biomass controls the carbon regime in a forest stand, tree standing stock and biomass structure (with regards to tree components) was estimated in young Norway spruce (Picea abies) stand based on repetitive tree sampling and allometric equations (modelled for 2009 and 2013). Large differences were found between the two models in the contribution of the tree components to above-ground biomass. Between the years 2009 and 2013, below-ground to above-ground biomass ratio dropped from 0.36 to 0.23 and short-lived to long-lived tree part ratio from 0.65 to 0.25. At the same time, the stand possibly reached maximum standing stock of both needles and fine roots. It is concluded that for biomass allocation estimates in young stands, not only stand-specific but also time-specific allometric relations should be constructed and implemented. Further, there appears to be a canopy closure threshold beyond which there is biomass allocation different from the status in sparse young spruce stands.